Cardiovascular Health in Children and Adolescents With Congenital Adrenal Hyperplasia Due to 21-Hydroxilase Deficiency - Improda, Nicola; Barbieri, Flavia; Ciccarelli, Gian Paolo; Capalbo, Donatella; Salerno, Mariacarolina (Frontiers in Endocrinology, 2019)
Increasing evidence indicate that adults with Congenital Adrenal Hyperplasia (CAH) may have a cluster of cardiovascular (CV) risk factors. In addition, ongoing research have highlighted that children and adolescents with CAH are also prone to develop unfavorable metabolic changes, such as obesity, hypertension, insulin insensitivity, and increased intima-media thickness, which place them at a higher risk to develop CV disease in adulthood. Moreover, CAH adolescents may exhibit subclinical left ventricular diastolic dysfunction and impaired exercise performance, with possible negative consequences on their quality of life. The therapeutic management of patients with CAH still remains a challenge and current treatment regimens do not always allow optimal biochemical control. Indeed, overexposure to glucocorticoids and mineralcorticoids as well as to androgen excess may contribute to the development of unfavorable metabolic and CV abnormalities. Long-term prospective studies on large cohorts of patients will help to clarify the pathophysiology of metabolic alterations associated to CAH. In the meanwhile, further efforts should be made in order to optimize treatment and identify new therapeutic approaches to prevent metabolic derangement and improve long-term health outcomes of CAH patients.